2015
DOI: 10.1093/cercor/bhv165
|View full text |Cite
|
Sign up to set email alerts
|

Default Mode Network Activity Predicts Early Memory Decline in Healthy Young Adults Aged 18–31

Abstract: Functional magnetic resonance imaging (fMRI) research conducted in healthy young adults is typically done with the assumption that this sample is largely homogeneous. However, studies from cognitive psychology suggest that long-term memory and attentional control begin to diminish in the third decade of life. Here, 100 participants between the ages of 18 and 31 learned Lithuanian translations of English words in an individual differences study using fMRI. Long-term memory ability was operationalized for each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 63 publications
3
20
0
Order By: Relevance
“…However, according to our results, some nodal metrics were significantly altered after two-year HA exposure (Tables 1 and 2) (Barber, Caffo, Pekar, & Mostofsky, 2017;Gotting et al, 2017;Nelson et al, 2016;Staffaroni et al, 2018). Moreover, the left anterior cingulate gyrus plays an important role in attentional control.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, according to our results, some nodal metrics were significantly altered after two-year HA exposure (Tables 1 and 2) (Barber, Caffo, Pekar, & Mostofsky, 2017;Gotting et al, 2017;Nelson et al, 2016;Staffaroni et al, 2018). Moreover, the left anterior cingulate gyrus plays an important role in attentional control.…”
Section: Discussionsupporting
confidence: 60%
“…Some brain regions were found to have both decreased degree centrality and nodal efficiency, including left insula, left anterior cingulate gyrus, left median cingulate gyrus, left hippocampus, left amygdala, left putamen, left Heschl, right temporal pole, left cerebelum_8, vermis_7, and vermis_8. The left insula, left anterior cingulate gyrus and left median cingulate gyrus all belong to default mode network which is tightly associated with memory and reaction (Barber, Caffo, Pekar, & Mostofsky, 2017; Gotting et al., 2017; Nelson et al., 2016; Staffaroni et al., 2018). Moreover, the left anterior cingulate gyrus plays an important role in attentional control.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, differences in sample age might be responsible as our sample was younger on average that than of Hu et al () (mean age 34.4 ± 8.6 years). Substantial age‐related changes have been reported in both PCu/PCC GABA+ concentration and DMN deactivation, even prior to middle age (Gao et al, ; Nelson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…PCu/PCC GABA+ concentration and DMN deactivation, even prior to middle age (Gao et al, 2013;Nelson et al, 2016).…”
Section: Substantial Age-related Changes Have Been Reported In Bothmentioning
confidence: 97%
“…Previous studies have shown that the deactivation of DMN is related with cognitive decline (Hansen et al, 2014;Nelson et al, 2016;Onoda et al, 2012;Vidal-Pineiro et al, 2014). Vincent et al (2010) demonstrated that DMN in human also exists in macaques under isoflurane (0.8-1.5%) in which PCC is shown as a dominant region in DMN.…”
Section: Long-duration Effect Of Isoflurane On Dmn Of the Brainmentioning
confidence: 98%